Application of discrete damage mechanics for determination of the crack density in composite laminates - Žmindák Milan; Kormaníková Eva; Novák Pavol; Soukup Josef; Kotrasová Kamila (MATEC Web of Conferences, 2020)
The finite element method (FEM) is one of the most widely and most popular numerical methods for analyzing damage of composite structures, In this paper discrete damage mechanics (DDM) is used to predict inter-laminar transverse and shear damage initiation and evolution in terms of the fracture toughness of the laminate. ANSYS commercial software is used for analysis of layered plate composite structure reinforced with long unidirectional fibers with Carbon/Epoxy material. Because ANSYS does not have a built-in capability for calculating crack density, we have to use plagin. A methodology for determination of the fracture toughness is based on fitting DDM model and these data are obtained from literature. Also, prediction of modulus vs. applied strain is contrasted with ply discount results and the effect of in situ correction of strength is highlighted. Evaluation of matrix cracking detected in lamina has been solved using return mapping algorithm.